Relaxation of thoracic aorta and pulmonary artery rings of marmosets (Callithrix spp.) by endothelium-derived 6-nitrodopamine - J. Britto-Júnior; A.T. Lima; J.S. Santos-Xavier; P. Gonzalez; F.Z. Mónica; R. Campos; V.B. de Souza; A.A. Schenka; E. Antunes; G. De Nucci (Brazilian Journal of Medical and Biological Research, 2023)
6-Nitrodopamine is a novel catecholamine released by vascular tissues, heart, and vas deferens. The aim of this study was to investigate whether 6-nitrodopamine is released from the thoracic aorta and pulmonary artery rings of marmosets (Callithrix spp.) and to evaluate the relaxing and anti-contractile actions of this catecholamine. Release of 6-nitrodopamine, dopamine, noradrenaline, and adrenaline was assessed by liquid chromatography with tandem mass spectrometry (LC-MS/MS). The relaxations induced by 6-nitrodopamine and by the selective dopamine D2 receptor antagonist L-741,626 were evaluated on U-46619 (3 nM)-pre-contracted vessels. The effects of 6-nitrodopamine and L-741,626 on the contractions induced by electric-field stimulation (EFS), dopamine, noradrenaline, and adrenaline were also investigated. Both aorta and pulmonary artery rings exhibited endothelium-dependent release of 6-nitrodopamine, which was significantly reduced by the NO synthesis inhibitor L-NAME. Addition of 6-nitrodopamine or L-741,626 caused concentration-dependent relaxations of both vascular tissues, which were almost abolished by endothelium removal, whereas L-NAME and the soluble guanylate cyclase inhibitor ODQ had no effect on 6-nitrodopamine-induced relaxations. Additionally, pre-incubation with 6-nitrodopamine antagonized the dopamine-induced contractions, without affecting the noradrenaline- and adrenaline-induced contractions. Pre-incubation with L-741,626 antagonized the contractions induced by all catecholamines. The EFS-induced contractions were significantly increased by L-NAME, but unaffected by ODQ. Immunohistochemical assays showed no immunostaining of the neural tissue markers S-100 and calretinin in either vascular tissue. The results indicated that 6-nitrodopamine is the major catecholamine released by marmoset vascular tissues, and it acts as a potent and selective antagonist of dopamine D2-like receptors. 6-nitrodopamine release may be the major mechanism by which NO causes vasodilatation.